Perancangan Keran Air Automatis Dengan Pelampung Vertikal Dengan Metode Design For Manufacturing And Assembly (DFMA) - M. Arif Munanda; Teuku Yasvi Ramadhana (Jurnal Teknik Mesin Unsyiah, 2020)
Up to to this day, the way we operate the water faucet ( open and close it) are still the same as it used to be for hundred of years. Because the faucets are easily damaged if they are rotated frequently, especially if the faucets rotated vigorously, it will likely to fail. Manually filling the water reservoir will also leave people to always be vigilant in monitoring the water level. People often forget or ignored to turn off the faucet when the water in the sink was full, so what happens is that the water is flowing out of the sink and will indirectly result in wasted water and electricity. If this continues to happen, it can be considered less effective and less efficient. This tool makes it easy for people to carry out water filling activities in the bath so that it can increase the effectiveness and efficiency as well as comfort in carrying out such activities.